"I Prefer Eating Less Than Eating Healthy": Drivers of Food Choice in a Sample of Muslim Adolescents - Lucie Nield (MDPI AG, 2024)
Adolescence is a time of significant change which is experienced differently across sociocultural contexts. Understanding drivers of food practice in adolescence is vital as these impact future health outcomes and can drive health inequality. This study investigates drivers of food choice in predominantly British-Asian, Muslim adolescents living in a deprived urban area of England. It identifies dominant drivers of food choice and their impact on health and wellbeing, and explores how Muslim adolescents from a low socioeconomic, British-Asian group understand and action autonomy in their food practices. PhotoVoice, a focussed ethnographical methodology where participants reflect on lived experience, was used to address the study aim. Participants (n = 21) were secondary school pupils aged 14-15 years, recruited from a school situated in an area of deprivation. Four overarching themes were developed from the qualitative data framework analysis: (1) food preference and other determinants of food choice; (2) concept, understanding and importance of health; (3) developing autonomy, skills, and independence; and (4) role of community, friends, and family in food practices. The adolescents were developing autonomy in relation to their food practices, whilst navigating a complex web of factors which were, in part, determined by their social class location and demographics. Participants understood the constituents of healthy eating. However, there was a perceived "effort" of being healthy, including additional time for preparing healthier food and sacrificing taste preferences. Parents, friends, and schools highly influence food choices, with adolescents preferring a broad palate of takeaway and convenience foods and would prefer to eat less of these "unhealthy" options than eat healthily.